Retrosternal goiter managed with endobronchial ultrasound-guided biopsy and transcervical resection: A case report (Indian Journal of Case Reports, 2026)
Retrosternal goiter is the extension of the thyroid tissue into the mediastinum. We present the case of a 48-year-old man who highlights the diagnostic challenges of such lesions, particularly in the absence of obvious visible neck swelling, and with only minimal symptoms. Subsequently, he presented for follow-up with progressive dyspnea, and repeat imaging revealed marked tracheal narrowing and a large mediastinal mass, raising suspicion for malignancy. Further evaluation with ultrasound, contrast-enhanced computed tomography (CT), and positron emission tomography-CT identified a large cervico-mediastinal thyroid mass with no fluorodeoxyglucose uptake. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) with rapid onsite cytology confirmed as a benign multinodular goiter. The patient underwent a successful transcervical total thyroidectomy, and the 9.8 cm mediastinal component was delivered through the neck without requiring sternotomy. This case highlights the role of EBUS-TBNA as a safe diagnostic tool for retrosternal lesions and also reinforces that even sizable intrathoracic goiters can often be managed through a cervical approach in experienced hands.